2019
DOI: 10.3346/jkms.2019.34.e111
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of the KDSQ-C, AD8, and SMCQ as a Cognitive Screening Test to Be Used in National Medical Check-ups in Korea

Abstract: Background Korea has a periodic general health check-up program that uses the Korean Dementia Screening Questionnaire-Cognition (KDSQ-C) as a cognitive dysfunction screening tool. The Alzheimer Disease 8 (AD8) and Subjective Memory Complaints Questionnaire (SMCQ) are also used in clinical practice. We compared the diagnostic ability of these screening questionnaires for cognitive impairment when completed by participants and their caregivers. Hence, we aimed to evaluate whether the SMCQ or AD8 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 18 publications
(25 reference statements)
0
27
0
Order By: Relevance
“…Both participants and informants separately completed the three questionnaires. Prior study for the comparative evaluation of questionnaires for screening cognitive dysfunction reported that informant‐ and self‐rated questionnaire scores had moderate correlations (Spearman correlation ρ = 0.522‐0.591, P < .001). In addition, correlations among three questionnaire scores were high for both self‐ratings ( ρ = 0.753‐0.804, all P < .001) and informant ratings ( ρ = 0.861‐0.890, P < .001) …”
Section: Methodsmentioning
confidence: 99%
“…Both participants and informants separately completed the three questionnaires. Prior study for the comparative evaluation of questionnaires for screening cognitive dysfunction reported that informant‐ and self‐rated questionnaire scores had moderate correlations (Spearman correlation ρ = 0.522‐0.591, P < .001). In addition, correlations among three questionnaire scores were high for both self‐ratings ( ρ = 0.753‐0.804, all P < .001) and informant ratings ( ρ = 0.861‐0.890, P < .001) …”
Section: Methodsmentioning
confidence: 99%
“…Our previous study found that the KDSQ-C had good discriminability for dementia. 2 The original version of the KD-SQ-C includes 15 questions that assess the 3 dimensions of memory impairment (items 1-5), other cognitive impairments including language impairments (items 6-10), and the ability to perform complex tasks in daily life (items 11-15). We divided the original version of the KDSQ-C into four subscales (I, II, III, and IV) and we compared the reliability and validity of each of these four subscales as a screening tool for cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed baseline demographic characteristics of the study participants were presented in our previous paper. 2 In brief, the sample consisted of 200 subjects with normal cognition, 50 patients with MCI, and 170 patients with dementia (Table 1). The mean age at the time of assessment was older and the educational level was lower in the dementia group than in the normal cognition group.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dementia screening test was evaluated using the KDSQ-C short form that includes five questions assessing memory impairment [ 23 ]. Response options of “never”, “sometimes”, and “frequently” are scored as 0, 1, and 2, respectively, and the cut-off values for dementia was a sum score >4 [ 24 ]. A score >4 in the KDSQ-C was defined as positive in the second NSPTA during the follow-up period.…”
Section: Methodsmentioning
confidence: 99%